Sarcosine is a prostate epigenetic modifier that elicits aberrant methylation patterns through the SAMe-Dnmts axis - Strmiska, Vladislav; Michalek, Petr; Lackova, Zuzana; Guran, Roman; Krizkova, Sona; Vanickova, Lucie; Zitka, Ondrej; Stiborova, Marie; Eckschlager, Tomas; Klejdus, Borivoj; Pacik, Dalibor; Tvrdikova, Eliska; et al. (Molecular oncology, 2019)
DNA hypermethylation is one of the most common epigenetic modifications in prostate cancer (PCa). Several studies have delineated sarcosine as a PCa oncometabolite that increases the migration of malignant prostate cells while decreasing their doubling time. Here, we show that incubation of prostate cells with sarcosine elicited the upregulation of sarcosine N-demethylation enzymes, sarcosine dehydrogenase and pipecolic acid oxidase. This process was accompanied by a considerable increase in the production of the major methyl-donor S-adenosylmethionine (SAMe), together with an elevation of cellular methylation potential. Global DNA methylation analyses revealed increases in methylated CpG islands in distinct prostate cell lines incubated with sarcosine, but not in cells of nonprostate origin. This phenomenon was further associated with marked upregulation of DNA methyltransferases (Dnmts). Epigenetic changes were recapitulated through blunting of Dnmts using the hypomethylating agent 5-azacytidine, which was able to inhibit sarcosine-induced migration of prostate cells. Moreover, spatial mapping revealed concomitant increases in sarcosine, SAMe and Dnmt1 in histologically confirmed malignant prostate tissue, but not in adjacent or nonmalignant tissue, which is in line with the obtained in vitro data. In summary, we show here for the first time that sarcosine acts as an epigenetic modifier of prostate cells and that this may contribute to its oncometabolic role.
Keywords: regulace genové exprese u nádorů; sarkosin; buněčné linie; prostata; Prostate; CpG ostrůvky; Up-Regulation; Gene Expression Regulation, Neoplastic; lidé; upregulace; Sarcosine; nádory prostaty; Prostatic Neoplasms; Cell Line; epigeneze genetická; CpG Islands; Male; mužské pohlaví; Epigenesis, Genetic; Humans